Advances in ionic liquids and deep eutectic solvents-based liquid phase microextraction of metals for sample preparation in Environmental Analytical Chemistry - Herce-Sesa, Belén; López-López, José A.; Moreno, Carlos (TrAC, Trends in analytical chemistry (Regular ed.), 2021)
Liquid phase micro-extraction (LPME) of metals has showed its potential for sample preparation in environmental analysis. In particular, the incorporation of ionic liquids to LPME (IL-LPME) has gotten increasing interest due to their unique properties as organic salts liquid at room temperature. In the last years, IL-LPME of metals has evolved to more efficient and selective extraction methods thanks to the development of task specific ionic liquids, and deep eutectic solvents. ILs have been implemented in the main LPME modalities: SDME, DLLME and HFLPME, resulting in new versions of these techniques. In this review we have analyzed and discussed the latest developments done in IL-LPME of metals, their advantages and limitations, as well as the potential fields of future development. •Ionic liquids expand the applicability of liquid microextraction of metals.•Ionic liquids are used in single drop, dispersive and hollow fiber microextraction.•Task specific ionic liquids improve the selectivity of microextraction systems.•Implementing ionic liquids has lead to new liquid microextraction modalities.•Ionic liquids open new stategies for metals analysis in environmental samples.